2006
DOI: 10.1186/ar2022
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to evaluate new and previously hypothesised non-genetic risk factors for serologic subtypes of rheumatoid arthritis (RA) defined by the presence or absence of auto-antibodies to cyclic citrullinated peptides (CCP). In a national case-control study, we included 515 patients recently diagnosed with RA according to the American College of Rheumatology 1987 classification criteria and 769 gender-and age-matched population controls. Telephone interviews provided information about non-genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(151 citation statements)
references
References 32 publications
(36 reference statements)
6
135
0
3
Order By: Relevance
“…Although the sample sizes of these studies were relatively small, it would be of interest to reanalyze them for effects of obesity/overweight on ACPA-positive and ACPA-negative RA. The only study that did investigate BMI in the 2 subgroups identified by ACPA status indeed found a similar association as in our study for ACPAnegative RA (18).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the sample sizes of these studies were relatively small, it would be of interest to reanalyze them for effects of obesity/overweight on ACPA-positive and ACPA-negative RA. The only study that did investigate BMI in the 2 subgroups identified by ACPA status indeed found a similar association as in our study for ACPAnegative RA (18).…”
Section: Discussionsupporting
confidence: 89%
“…One relatively small case-control study (18) found an association of being overweight or obese to be confined to those with anti-citrullinated protein antibody (ACPA)-negative RA, a subgroup analysis that was not carried out in the earlier studies. Recent data on the major etiologic differences between ACPA-positive and ACPA-negative RA (19) have emphasized that analyses of potential risk factors for RA should always include a separate analysis of these disease subsets.…”
Section: Introductionmentioning
confidence: 98%
“…Age at menarche is a key characteristic of initiating time episode of exposing to increased rates of female hormones may influence the risk of RA (11)(12)(13)(14). Nevertheless, females who were at younger ages for menarches were expected to be at higher risk for RA development (6,15,16), some researchers described the increasing risk of the disease by being at older ages for the physiological commencing of mense (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, females who were at younger ages for menarches were expected to be at higher risk for RA development (6,15,16), some researchers described the increasing risk of the disease by being at older ages for the physiological commencing of mense (11)(12)(13)(14). Age at menopause is supposed as another key determinant of estrogen exposing period in lifetime to raise the RA incidence (15).…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced risk of Graves’ hyperthyroidism up to 12 months post-partum is well known [5, 9] but it is not known whether this risk extends more than a year after delivery [10]. Age at menarche [11-13], age at menopause [12, 13], and the use of oral contraceptives (OC) [11, 12] have all been associated with altered risk for autoimmune diseases. A few studies examined the association between delivery and later development of Graves’ hyperthyroidism [5, 10, 14, 15], but no study has extensively investigated the long-term repercussions of multiple reproductive factors on the risk of developing various types of hyperthyroidism.…”
Section: Introductionmentioning
confidence: 99%